Attitudes of health professions students towards interprofessional education - Causapin, Anna Karenina V.
Interprofessional education (IPE) occurs when students of two or more professions learn with, from and about each other to improve collaboration and the quality of care (CAIPE, 2002). The thrust of IPE is to prepare the health professions (HP) students to be able to deliberately work together in a collaborative manner, with a common goal of providing better and safer patient care. This study aimed to determine the awareness of the HP students about IPE, describe and differentiate their attitudes according to sex, course, year level, prior clinical and IPE experiences, and level of moral development, and determine which of the the aforementioned variables can predict the attitude on IPE. Correlational study was done among HP students using a validated three- part Interprofessional Education Attitude Scale (IPE-AS). Of the 485 participants, 85% were aware of IPE. No significant difference was found between HP students? attitudes and sex (p value=0.56) and prior IPE experience (p value=0.81). However, there were significant differences noted in the students? perception of IPE according to course (p value=0.0005), year level (p-value=0.001), and level of moral development (p value=0.0001) . The medicine students were found to have the most favorable attitudes towards IPE (Mean=44.86 ± 5.62), followed by pharmacy (Mean=42.99 ± 5.37)and nursing (Mean=42.36 ± 7.44) students. Students in year levels I (Mean=45.60 ± 3.54) and II (Mean=45.35 ± 3.64) were found to have more favorable attitudes on IPE than those in year levels III (Mean=42.91 ± 6.83) and IV (Mean=43.66 ± 6.53). xiiiStudents in the conventional (Mean=43.13 ± 5.12) and postconventional levels (Mean=44.58 ± 5.85) of moral development have favorable attitudes while those in the preconventional level (Mean=39.33 ± 9.04) have unfavorable attitudes on IPE. Multivariate analysis showed significant differences in the course (p value=0.05) , year level (p value=0.04), and level of moral develoment (p value=0.0001) and are shown to be predictors of attitudes towards IPE. Based on the results, HP students have favorable attitudes towards IPE, indicative of their readiness to learn the concept. This would guide the curriculum developers in the explicit integration of IPE in the HP curricula.